Rocambole dalam bahasa Melayu: satu kajian awal - Zaini-Lajoubert, Monique (Universiti Kebangsaan Malaysia, 2001)
Rocambole is a French serial written by Ponson du Terrail (1829-1871). It is so popular that it has been translated into many languages, including Malay. There are two Malay versions of this serial, namely a Malaysian and an Indonesian, both of which have not been studied in depth. This article endeavours to analyse both versions from several aspects, including the writer of Rocambole, Ponson du Terrail, the translators/adaptators of the Malay versions, Syed Syeikh bin Syed Ahmad al-Hadi and Lie Kim Hok, and the original French serial. A comparison of the two Malay versions is also attempted